Cinematic tourist mobilities and the plight of development : on atmospheres, affects and environments - Tzanelli, Rodanthi, 1974- (London : Routledge, 2019)
It is said that movies have encroached upon social realities creating tourism enclaves based on distortions of history and heritage, or simulations that disregard both. What localities and nation-states value are discarded, suppressed, or modified beyond recognition in neoliberal markets; thus flattening out human experience, destroying natural habitats in the name of development, and putting the future of whole ecosystems at risk. Without disregarding such developmental risks Cinematic Tourist Mobilities and the Plight of Development explores how, en route to any beneficial or eco-destructive development, film tourist industries co-produce atmospheres of place and culture with tourists/film fans, local activists, and nation-states. Drawing on international examples of cinematically-induced tourism and tourismophobic activism, Tzanelli demonstrates how the allegedly unilateral industry-driven 'design' of location stands at a crossroads between political structures, systems of capitalist development, and resurgent localised agency. With an interdisciplinary methodological and epistemological portfolio connected to the new mobilities paradigm, this volume will appeal to scholars, students, and practitioners interested in tourism, migration, and urban studies in sociology, anthropology, geography, and international relations.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism and motion pictures; Tourism -- Environmental aspects; Economic development -- Environmental aspects; Culture and tourism; BUSINESS & ECONOMICS / Industries / General; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General